DOI: 10.31274/etd-180810-4864
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the gallbladder host environment and small RNAs in the pathobiology of Campylobacter jejuni sheep abortion clone IA 3902

Abstract: Campylobacter jejuni is an important zoonotic agent that is the leading cause of both human foodborne bacterial gastroenteritis worldwide, as well as ovine abortion in the United States. In particular, a single C. jejuni sheep abortion clone, of which IA 3902 is a prototypical isolate, has recently emerged as the dominant causative agent of sheep abortion due to Campylobacter sp. in the U.S. and has been increasingly identified in human outbreaks of disease. Multi-omics approaches to studying this hypervirulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 166 publications
(301 reference statements)
0
1
0
Order By: Relevance
“…In a study of the abortifacient sheep clone IA 3902 [85] flgK and nuo genes were expressed at a higher level than in NCTC 11168 and iron acquisition genes were expressed at a lower level. Further study also identified upregulation of nrfA in this strain [86]. A study of the genes involved in response to acidic pH and stomach transit [52] identified changes in the expression of htpX , nrfA and cft as important for stomach transit and mreC , which is also involved in cell shape, as influenced by acid shock.…”
Section: Resultsmentioning
confidence: 85%
“…In a study of the abortifacient sheep clone IA 3902 [85] flgK and nuo genes were expressed at a higher level than in NCTC 11168 and iron acquisition genes were expressed at a lower level. Further study also identified upregulation of nrfA in this strain [86]. A study of the genes involved in response to acidic pH and stomach transit [52] identified changes in the expression of htpX , nrfA and cft as important for stomach transit and mreC , which is also involved in cell shape, as influenced by acid shock.…”
Section: Resultsmentioning
confidence: 85%